Effect of β-aminobutyric acid (BABA) on protection against Phytophthora infestans throughout the potato crop cycle - Altamiranda, E.A.G. (2008)
The protective effect of â-aminobutyric acid (BABA) on two potato cultivars (Bintje and Pampeana) with different level of horizontal resistance against Phytophthora infestans was investigated during the crop cycle. Plants were treated with BABA 16, 23, 30, 38, 44, 51, 61 or 75 days after emergence. After each application, the percentage of protection and the content of glucanases, chitinases and phenolic compounds were determined in detached leaves. The foliar pretreatment with BABA up to 30 days after emergence showed a 60% protection percentage against P. infestans in cv. Pampeana, while cv. Bintje almost reached 20%. The results indicated that the time of application of BABA and the susceptibility of the cultivars affect both, the protection against late blight and the expression of defense molecules like glucanases, chitinases and phenolic compounds.